Effects of social media sponsorship disclosure on adolescents’ advertising literacy and purchase intention - Ya-En Catherine Lin; Fong-Ching Chang; Tzu-Fu Huang; Shawn C. Chiang; Chiung-Hui Chiu; Ping-Hung Chen; Nae-Fang Miao; Hung-Yi Chuang (PLoS ONE, 2026)
Introduction In the rapidly evolving digital age, adolescents have become a particularly vulnerable group impacted by social media marketing. This study aims to examine how different types of sponsorship disclosure (full, partial, and none) in social media affect adolescents’ ability to recognize advertising, their advertising literacy, and their purchase intentions. Materials and methods A self-administered questionnaire was used to assess the effects of three types of sponsorship disclosure in social media posts on adolescents. In 2022, a total of 3,149 high school students were recruited from 36 schools across Taiwan using a probability proportional to size sampling method. Adolescents were randomly assigned to one of three experimental groups and exposed to social media posts featuring varying levels of sponsorship disclosure. Results The study found that adolescents exposed to full sponsorship disclosure had significantly higher rates of advertisement recognition and greater conceptual advertising literacy compared to those in the partial or no disclosure conditions. The multivariate analysis revealed that advertisement recognition was associated with higher levels of both conceptual and attitudinal advertising literacy. Adolescents who could recognize advertisements demonstrated higher attitudinal advertising literacy, which was associated with lower purchase intentions. Conclusions Clear sponsorship disclosure is crucial for raising advertising awareness among adolescents, enhancing their advertising literacy, and potentially protecting them from increased susceptibility to purchase intentions.